Gram-negative bacterial endocarditis in adults: state-of-the-heart - Raza, Sania S; Sultan, Omer W; Sohail, Muhammad R (Expert review of anti-infective therapy, 2010)
Gram-negative endocarditis due to HACEK bacteria (Haemophilus species, Actinobacillus, Cardiobacterium, Eikenella and Kingella species) and non-HACEK organisms is an infrequent occurrence but is associated with significant morbidity and mortality. Traditionally, non-HACEK Gram-negative endocarditis has been associated with injection drug use. However, emerging data from more contemporary cohorts suggest changing epidemiology and risk factors for Gram-negative endocarditis, necessitating an updated review of this subject. Moreover, optimal management, including the need for surgical intervention, and strategies for the prevention of Gram-negative endocarditis need to be revisited.